Tập thô trong bảng quyết định - Hà, Quang Thụy (Đại học Quốc gia Hà Nội, 2014)
Decision Tables has been carried out by S. Pollack, H. Hicks and W.Harrison, Pawlak gave some notations of the rough set into the decision tables in order to study the learning problem. The concept of the attribute dependence also has been carried on by W. Pawlak. In this article, we show two algorithms to determine the attribute dependence, also for the complete dependence and the other for the rough (parthly) dependence. We are study some characters of the dependence for Armstrong's axioms: the transmissive axioms is lost by the rough dependence.